THE MIDDLE-UPPER TRIASSIC OF THE SAN DONATO UNIT AUCT. (NORTHERN CALABRIA): STRATIGRAPHY, PALEOGEOGRAPHY AND TECTONIC IMPLICATIONS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1995)
In this paper are presented  stratigraphic and sedimentological data on the carbonate successions occurring in the Cozzo del Pellegrino massif (Cosenza), generally considered as pertaining to the metamorphic San Donato Unit. The successions start with thick phyllites and intercalated carbonate lenses containing Anisian-lower Ladinian algae. To the phyllites follows the informally defined calcari formation, locally occurring also as its lateral equivalent. The calcari formation  consists of two members, the first of which (Piano del  Minatore Mbr.)consists of black, often marly limestones, showing nodular and bioturbated textures, with a scarce and banal fauna represented by ostracods, gastropods and bivalves. Algal mounds, with porostromata and crinoids are locally intercalated in these facies. In the upper part of the formation the black limestones pass laterally to a reef complex  (Monte Caramolo Mbr.) of Ladino-Carnian age, consisting mainly of boundstones with sponges and biogenic crusts, as well as of fore-reef  breccias. These lithotypes have been interpreted as deposited on a carbonate ramp evolving to a restricted, poorly oxygenated lagoonal area, bordered by bioconstructed margins. In the lower Carnian a carbonate-marly horizon, containing traces of evaporites, whose thickness is decreasing toward the east, allows a lithostratigraphic correlation betweenmost of the studied successions. The calcari formation is followed by the Scifarello formation, mainly outcropping in the eastern parts of the studied area. It consists generally of tidal dolomites with some tempestites deposited on an shallow open  shelf, followed by dolomites and laminated, often marly, dolomitic limestones, deposited in a subtidal, restricted environment. On the basis of foraminifers and bivalves data, the upper part of the Scifarello formation has been  ascribed to the upper Carnian-Norian. Moreover, a strong tectonic activity of Lower Norian age is evidenced by the presence of mass-flows and sedimentary dikes in the more easterly areas of the massif. The general paleoenvironmental evolution, in the period spanning between Anisian and Early Norian, can be envisaged firstly in a carbonate sedimentation on a wide shelf, grading toward the east to deeper, possibly  basinal areas, whose location was controlled by the Ladinian  and/or Norian synsedimentary tectonics. This shelf was bordered on the west by a peri-continental area, with silicoclastic to evaporitic deposits, better represented in the Cetraro area. Finally, the Norian dolomites  pertaining to the Verbicaro Unit, usually considered as have been thrusted onto rhe Triassic carbonates of the San Donato Unit, have been often observed to occur in normal stratigraphical superposition over the latter. Therefore, also considering the ambiguous evidence presented in the literature on the Jurassic-Miocenic evolution of the San Donato Unit AUCT, we interpret the Norian Verbicaro dolomites as being the most natural evolution of the Anisian-Lower Norian San Donato lithotypes. It follows that for a really valid paleogeographic reconstruction a complete redefinition of the tectonic units in the whole area is needed.
Keywords: Middle Triassic; Upper Triassic; Southern Apennines; San Donato Unit; Calabria; PaleogeographY; Carbonate Platform; Evaporites.